2013
DOI: 10.1346/ccmn.2013.0610102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antimonate, Arsenate, and Phosphate on the Transformation of Ferrihydrite to Goethite, Hematite, Feroxyhyte, and Tripuhyite

Abstract: Iron oxides, typical constituents of many soils, represent a natural immobilization mechanism for toxic elements. Most iron oxides are formed during the transformation of poorly crystalline ferrihydrite to more crystalline iron phases. The present study examined the impact of well known contaminants, such as P(V), As(V), and Sb(V), on the ferrihydrite transformation and investigated the transformation products with a set of bulk and nano-resolution methods. Irrespective of the pH, P(V) and As(V) favor the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…Based on a review of the literature, we found several studies describing the transformation of goethite to other iron (hydr)oxide minerals in alkaline solution 16 , 40 – 42 . The inter-transformation among various iron (hydr)oxides is a well-known environmental phenomenon, and this transformation plays a key role in maintaining the ecosystem by retaining nutrients and pollutants and involving oxidation and reduction 15 , 16 , 43 . For that reason, we suspected that contamination occurred during the experiment or drying process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a review of the literature, we found several studies describing the transformation of goethite to other iron (hydr)oxide minerals in alkaline solution 16 , 40 – 42 . The inter-transformation among various iron (hydr)oxides is a well-known environmental phenomenon, and this transformation plays a key role in maintaining the ecosystem by retaining nutrients and pollutants and involving oxidation and reduction 15 , 16 , 43 . For that reason, we suspected that contamination occurred during the experiment or drying process.…”
Section: Resultsmentioning
confidence: 99%
“…Ralph et al . 16 examined the effects of antimonate, arsenate and phosphate on the transformation of iron (hydr)oxides, and their results showed that arsenate and phosphate favoured the formation of haematite over goethite from ferrihydrite, but no transformation occurred at high concentrations (above 2.25 mM). In our laboratory, we also had 30-nm haematite purchased from US nano (US3160, USA), which had similar d-spacing values of 1.84, 2.51 and 2.70 Å, as determined by X-ray diffraction (XRD) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Bolanz et al (2013a, b), the presence of oxyanions, concentration and pH controlled the transformation of iron (hydr)oxides via various processes, and much attention was dedicated to determining the stability of the iron (hydr)oxides in the adsorption experiments. Based on their studies, a high concentration (6 mM) of arsenate and phosphate blocked the transformation from ferrihydrite to other species, but a high concentration (6 mM) of antimonate led to transformation to feroxyhyte (Bolanz et al 2013b;Michael Bolanz et al 2013). The authors also examined the effect of pH and observed transformation from ferrihydrite to hematite at pH 4 and to goethite at pH 12, while transformation to both hematite and goethite was observed at pH 7.…”
Section: Physiochemical Transformation Of Iron (Hydr)oxidesmentioning
confidence: 99%
“…Based on studies examining the effect of oxyanions on the transformation of iron (hydr)oxides, the pH, type and concentration of oxyanions controlled the transformation from ferrihydrite to goethite, hematite or feroxyhyte (Michael Bolanz et al 2013). Unlike the result by Han and Ro (2018a), a high concentration of oxyanions suppressed the transformation of ferrihydrite except the antimony-based oxyanion, which led to feroxyhyte formation at high concentrations only.…”
Section: Transformation Of Iron (Hydr)oxides and Their Colloidal Mobimentioning
confidence: 99%
“…It plays an essential role as a sorbent of various major and trace elements and controls their availability in the environment [7][8][9][10][11]. Therefore, natural ferrihydrite always contains a variety of impurities that affect its chemical and physical properties [12][13][14][15][16][17][18][19]. Some impurities such as phosphate are important nutrients, while other impurities may be unwanted compounds, toxic metals and metalloids (e.g., Cd, Pb, As).…”
Section: Introductionmentioning
confidence: 99%